2016
DOI: 10.1002/hbm.23293
|View full text |Cite
|
Sign up to set email alerts
|

Altered Integration of Structural Covariance Networks in Young Children With Type 1 Diabetes

Abstract: Type 1 diabetes mellitus (T1D), one of the most frequent chronic diseases in children, is associated with glucose dysregulation that contributes to an increased risk for neurocognitive deficits. While there is a bulk of evidence regarding neurocognitive deficits in adults with T1D, little is known about how early-onset T1D affects neural networks in young children. Recent data demonstrated widespread alterations in regional gray matter and white matter associated with T1D in young children. These widespread ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 84 publications
(153 reference statements)
3
27
0
Order By: Relevance
“…Consistent with this notion, several studies [5,6], including research from our group [713], have observed altered brain structure in children with T1D relative to age- and sex-matched healthy controls. Cross-sectional investigations indicate that these changes originate shortly after diagnosis and last well into adulthood [14,15].…”
Section: Introductionsupporting
confidence: 81%
“…Consistent with this notion, several studies [5,6], including research from our group [713], have observed altered brain structure in children with T1D relative to age- and sex-matched healthy controls. Cross-sectional investigations indicate that these changes originate shortly after diagnosis and last well into adulthood [14,15].…”
Section: Introductionsupporting
confidence: 81%
“…Such researches have promoted the quantification of anatomical links among cortical parcellations based on inter-regional covariation of various morphometric features, such as CT. A vital assumption underlying structural covariance networks (SCNs) is that the morphological characteristics of inter-areal gray matter would covary since they share common development, maturation and disease propagation effects (Raznahan et al, 2011; Alexander-Bloch et al, 2013; DuPre and Spreng, 2017; Liu et al, 2019). It has also been reported that SCNs correspond with anatomical and functional networks constructed through white matter tractography (Hosseini et al, 2016; Bruno et al, 2017).…”
Section: Introductionmentioning
confidence: 79%
“…D max was set to 0.5 given that above this threshold the graphs become increasingly random . Within the adjacency matrix A , the diagonal elements (ie, self‐connections) and negative correlations were set to 0 since the biological meaning of negative correlations in structural correlation networks is unclear . Binary association matrices were used given the methodological concerns when comparing weighted matrices .…”
Section: Methodsmentioning
confidence: 99%
“…41,44 Within the adjacency matrix A, the diagonal elements (ie, self-connections) and negative correlations were set to 0 since the biological meaning of negative correlations in structural correlation networks is unclear. 28,45 Binary association matrices were used given the methodological concerns when comparing weighted matrices. 46 Adjacency matrix A represented a binary undirected graph G in which i and j were connected if g ij was equal to 1.…”
Section: Structural Network Constructionmentioning
confidence: 99%
See 1 more Smart Citation